Environmental ethics : - Pojman, Louis P. (Thomson Wadsworth, 2008)
The most comprehensive introduction to environmental ethics available, ENVIRONMENTAL ETHICS offers students a current look at the issues and topics that dominate the field today, organized into two main parts that take students seamlessly from theory to application. This Fifth Edition of the Pojmans' popular anthology, like its predecessors, includes numerous topic areas not covered in other anthologies-including an all-new section on Climate Change. Featuring articles carefully selected for clarity and accessibility, the text follows a dialogic pro-con format presenting divergent positions on each topic, ensuring that students are both exposed to and understand both sides of every topic so they can develop their own informed positions. The bulk of royalties for this book are donated to groups dedicated to protecting the environment, such as the Wilderness Society and the Sierra Club.